2008
DOI: 10.4049/jimmunol.181.2.1245
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the MD-2/TLR4 Interface Required for Signaling by Lipid IVa

Abstract: LPS signals through a membrane bound-complex of the lipid binding protein MD-2 and the receptor TLR4. In this study we identify discrete regions in both MD-2 and TLR4 that are required for signaling by lipid IVa, an LPS derivative that is an agonist in horse but an antagonist in humans. We show that changes in the electrostatic surface potential of both MD-2 and TLR4 are required in order that lipid IVa can induce signaling. In MD-2, replacing horse residues 57-66 and 82-89 with the equivalent human residues c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
137
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 41 publications
6
137
0
1
Order By: Relevance
“…Lipid IV A is a partial agonist in equine cells (19). However, similar to human MD-2, equine MD-2 has the positively charged Arg-122 at the hydrophobic pocket entrance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid IV A is a partial agonist in equine cells (19). However, similar to human MD-2, equine MD-2 has the positively charged Arg-122 at the hydrophobic pocket entrance.…”
Section: Discussionmentioning
confidence: 99%
“…Human MD-2 has positively charged Lys-125 at the dimerization interface close to the pocket entrance, whereas mMD-2 has hydrophobic Leu-125 at this position. A little further away from the pocket entrance, hMD-2 has positively charged Lys-58 on the ␤4 strand that has been implicated in lipid IV A discrimination (19), whereas mMD-2 has negatively charged Asn-58 at this position. Because the acyl chains of LPS bind to the MD-2 hydrophobic pocket, and the diglucosamine backbone of LPS sits next to the pocket entrance (12,13), modifications of MD-2 surface charges at residues 122, 125, and 58 likely affect lipid binding and directly influence lipid IV A species specificity.…”
Section: Human and Mouse Md-2 Have Different Surface Chargesmentioning
confidence: 99%
“…In particular, it acts as a weak agonist on mouse and as an antagonist on human cells (20,21). Although several studies have investigated the species-specific activity of lipid IVa (22)(23)(24)(25)(26)(27)(28), these studies primarily used mutational and computational simulation methods. Structural information on the agonistic form of TLR4/MD-2 is limited to the hTLR4/MD-2/LPS complex; no structures of mTLR4/MD-2 complexed with LPS or lipid IVa are currently available.…”
mentioning
confidence: 99%
“…These results are in accordance with studies showing that different lipid A-derived structures can be TLR4/MD-2 agonists or antagonists and others TLR2 agonists. The critical factors for their agonistic versus antagonistic effects and their promiscuity for TLR2 versus TLR4 are the number of acyl chains, the length of the carbon chains, the number and the distribution of negative charges, the asymmetry of the acyl chains, and the species of TLR4 (5)(6)(7)(8). It has been shown that lipid IVa, for example, can be an agonist in mouse and horse TLR4/MD-2 but is clearly an LPS antagonist in human TLR4/ MD-2 (8,20).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for TLR2 and TLR4, which have been crystallized with their respective ligands (2,4). Individual LPS molecules may act as agonists in some mammalian species and as antagonists in others (5)(6)(7)(8). As an example, monomerized LPS binds CD14 and is then transferred onto MD-2 and TLR4.…”
mentioning
confidence: 99%